Psychometric properties of the English and Hindi versions of the Brief Inventory of Thriving for use among Indian adolescents - Usama Ghayas Syed; Shikha Dixit; Margaret L. Kern (Scientific Reports)
Abstract The Brief Inventory of Thriving (BIT) provides a holistic measure of well-being, but has only been validated for adults, and does not have a Hindi version. The present study investigated the unidimensional structure, internal consistency, convergent/discriminant, and criterion validity of both the original English version of the BIT (BIT-E) and its Hindi-translated version (BIT-H) among adolescents in India. Further, we tested measurement invariance across these two language versions, gender, and academic disciplines. A total of 534 adolescents were recruited across two samples (N 1  = 224 and N 2 = 310) from five schools using convenience sampling. Both versions demonstrated excellent psychometric properties, with unidimensional structure, good internal consistency, convergent/discriminant, and criterion validity with a number of psycho-educational correlates. Partial scalar invariance was achieved across language versions and gender, while strict invariance was established across academic disciplines. The BIT, in both English and Hindi, appears to be an excellent measure of well-being for adolescents. Limitations, directions for future research, and recommendations for using the BIT-E and BIT-H among adolescents in research and applied settings are discussed.